2022
DOI: 10.1182/bloodadvances.2021006456
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Y chromosome before allogeneic hematopoietic stem cell transplantation in male recipients with female donors

Abstract: The graft-versus-leukemia (GVL) effect is one of the curative mechanisms of allogeneic hematopoietic stem cell transplantation (allo-HCT). H-Y antigens, which are encoded by Y chromosome, are important targets of the GVL effect. Thus, deletion of the Y chromosome (del[Y]) might cause the GVL effect to deteriorate in a transplantation involving a female donor and male recipient, although the clinical significance of the del(Y) group remains to be elucidated. In this study, we evaluated adult male patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…On the other hand, some previous studies showed a reduced incidence of relapse which suggested the existence of a GVL effect due to sex-mismatch 8 , 24 26 . In fact, we previously reported that male recipients with deletion of Y-chromosome who underwent allo-HCT from a female donor showed a higher incidence of relapse 12 , suggesting attenuation of the GVL effect due to the loss of Y-chromosome. Thus, we initially hypothesized that the addition of ATG may contribute to a lower incidence of chronic GVHD and a higher incidence of relapse in female-to-male allo-HCT.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, some previous studies showed a reduced incidence of relapse which suggested the existence of a GVL effect due to sex-mismatch 8 , 24 26 . In fact, we previously reported that male recipients with deletion of Y-chromosome who underwent allo-HCT from a female donor showed a higher incidence of relapse 12 , suggesting attenuation of the GVL effect due to the loss of Y-chromosome. Thus, we initially hypothesized that the addition of ATG may contribute to a lower incidence of chronic GVHD and a higher incidence of relapse in female-to-male allo-HCT.…”
Section: Discussionmentioning
confidence: 97%
“…It may be reasonable to try to improve the survival inferiority of female-to-male allo-HCT by intensive GVHD prophylaxis. However, since previous reports have suggested a relationship between H-Y antigens and a graft-versus leukemia (GVL) effect 10 , 12 , an escalation of GVHD prophylaxis might induce an increased incidence of relapse in addition to infectious complications. We hypothesized that the use of ATG in female-to-male allo-HCT may contribute to a lower incidence of chronic GVHD and a higher incidence of relapse, and the prognosis in female-to-male allo-HCT may depend on which of these effects is predominant.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some previous studies showed a reduced incidence of relapse which suggested the existence of a GVL effect due to sex-mismatch 8, [23][24][25] . In fact, we previously reported that male recipients with deletion of Y-chromosome who underwent allo-HCT from a female donor showed a higher incidence of relapse 12 , suggesting attenuation of the GVL effect due to the loss of Y-chromosome. Thus, we initially hypothesized that the addition of ATG may contribute to a lower incidence of chronic GVHD and a higher incidence of relapse in female-to-male allo-HCT.…”
Section: Discussionmentioning
confidence: 97%